PENGARUH FAKTOR KEUANGAN TERHADAP MANAJEMEN LABA MENGGUNAKAN PENDEKATAN TEORI FRAUD TRIANGLE - Ignatius Oki Dewa Brata; Komarudin Komarudin (Jurnal Computech & Bisnis (e-Journal), 2022)
The objective of the research is to examine whether financial factors seen by fraud triangle theory perspective effect to earning management, within Good Corporate Governance as a moderator variable. Financial factor variables consists of Free cash flow as an opportunity in fraud triangle theory, leverage as a pressure and profitability as a rationalitaion from fraud triangle theory. This research is a quantitative research used descriptif method. The population on this study are banks that actively listed on the IDX period 2016 to 2018. This sample is taken by purposive sampling method within 102 bank samples. Data analysis used multiple linear regression and moderation regression. The results showed that free cash flow had a positive effect on earnings management, the leverage had no effect on earnings management, and the profitability had a negative effect on earnings management. Keywords: Earnings management, free cash flow, leverage, profitability